Analysis of Variations Apparent Diffusion Coefficient (ADC) Values in Brain Areas Using Dwi Resolve Sequence - Chankrisna Anggarayuda; Hernastiti Sedya Utami; Kusnanto Mukti Wibowo; Pradana Nur Oviyanti; Fathur Rahman Nugraha (Jurnal Health Sains, 2026)
Magnetic Resonance Imaging (MRI) with Diffusion-Weighted Imaging (DWI) evaluates the microstructure of brain tissue through the Apparent Diffusion Coefficient (ADC) parameter. Although often used clinically, the accurate standardization of physiological values of ADCs is still a challenge due to the high regional variability. This study aims to analyze the difference in ADC values in various anatomical structures of the adult brain using the DWI Readout Segmentation of Long Variable Echo-trains (RESOLVE) sequence. This retrospective analytical observational study involved 12 normal subjects examined using 1.5 Tesla MRI. Measurements were made manually on 14 anatomical structures using a circular Region of Interest (ROI) (±20 mm²). Reliability is validated by the Intraclass Correlation Coefficient (ICC). Statistical analysis included Repeated Measures ANOVA, Spearman correlation (age), and Wilcoxon test (grey vs White matter). The results showed that the ROI had excellent reliability (ICC 0.845–0.998). There was a very significant difference in ADC values between anatomical structures (p < 0.001; Partial η² = 0.700), with an average range of 0.70–0.83 ×10⁻³ mm²/s. There was no significant correlation between age (22–68 years) and regional ADC fluctuations (p > 0.05). However, the ADC of Grey matter was found to be significantly higher than that of White matter (p = 0.002). In conclusion, the RESOLVE DWI sequence results in reliable ADC measurements. Variations in diffusion values are inherently dependent on anatomical location and tissue type, but are very stable with age.